Malevolent Creativity and Malevolent Innovation: A Critical but Tenuous Linkage. Issue 2 (3rd April 2022) - Hunter, Samuel T.; Walters, Kayla; Nguyen, Tin; Manning, Caroline; Miller, Scarlett
ABSTRACT: Interest is growing in the dark side of creativity and recent research has been instrumental in improving our understanding of the phenomenon. However, such efforts have also revealed confusion regarding the definition and operationalization of the dark side of creativity and malevolent creativity in particular. In response, we offer definitional clarity for both the generation of novel, malevolent ideas (i.e., malevolent creativity) as well as the implementation of those ideas (i.e., malevolent innovation). In addition, we present a framework outlining how and why malevolent ideas transition from ideation to implementation. This framework considers influences linked to both ability and willingness to engage in malevolent processes, spanning intrapersonal and interpersonal factors. Our review reveals a complex but tenuous link between malevolent creativity and innovation and one that requires consideration of the processes connecting the two. Moreover, our review of the malevolent creative processes suggest that we have unintentionally avoided uncomfortable truths around who is capable of generating and instantiating malevolent ideas. Implications and a plan for moving research forward are discussed.